2011
DOI: 10.3174/ajnr.a2816
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of the Inferior Intercavernous Sinus: A New Sign for the Diagnosis of Craniospinal Hypotension

Abstract: We read with interest the recent article entitled "MR Imaging of the Optic Nerve Sheath in Patients with Craniospinal Hypotension" by Rohr et al. 1 In patients with craniospinal hypotension, apart from engorged venous sinuses, enlarged pituitary gland, subdural effusions, and sagging of the brain, the authors have observed a partially or fully collapsed intersheath space of the optic nerves. Such a demonstration is particularly clear in their Fig 3. We would like to draw more attention to changes in the pituit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Most studies reporting on the change in brain MRI after treatment focus on single imaging findings. [15][16][17] This may be inadequate, since none of the signs is pathognomonic, and, in our experience, some signs are subject to poor interobserver agreement. [8] As previously reported, the bSIH score is a reliable and objective tool to assess 13 the likelihood of spinal CSF loss in patients with orthostatic headache at baseline.…”
Section: Discussionmentioning
confidence: 81%
“…Most studies reporting on the change in brain MRI after treatment focus on single imaging findings. [15][16][17] This may be inadequate, since none of the signs is pathognomonic, and, in our experience, some signs are subject to poor interobserver agreement. [8] As previously reported, the bSIH score is a reliable and objective tool to assess 13 the likelihood of spinal CSF loss in patients with orthostatic headache at baseline.…”
Section: Discussionmentioning
confidence: 81%
“…3 Enlargement of the IIS on MRI is associated with intracranial hypotension, and a change in size may be detected with treatment of the underlying pathology. 18,19 The basilar sinus. Although not part of the circular sinus, the basilar sinus (BS), which lies posterior to the clivus and connects the posterior aspect of both cavernous sinuses, is the largest and most constant of all the intercavernous sinuses.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3 Enlargement of the IIS on magnetic resonance imaging (MRI) is associated with intracranial hypotension, and a change in size may be detected with the treatment of the underlying pathology. 18,19 The Basilar Sinus…”
Section: The Anterior Intercavernous Sinusmentioning
confidence: 99%
“…A dilated inferior intercavernous sinus has been found on MR venography in several studies in which patients experienced intracranial hypotension [1,3,5]. Although some masses of the sella can compress the intercavernous sinuses making them smaller [9,11,22,33], certain pathologies such as carotid-cavernous fistulas can enlarge these structures [4,11,31,32].…”
Section: Clinical and Surgical Significancementioning
confidence: 99%
“…Encounters with the inferior intercavernous sinus mainly occur during transsphenoidal surgery for pituitary tumors [2]. Several studies have shown that dilated inferior intercavernous sinuses are found in patients with intracranial hypotension [1][2][3][4][5][6]. Mizutani et al suggest that the literature regarding this structure is because of its deep location within the skull base and its infrequent visualisation in open craniotomies [5,7].…”
Section: Introductionmentioning
confidence: 99%